Supervisi Edukatif Kolaboratif untuk Meningkatkan Kinerja Guru Menyusun dan Melaksanakan Pembelajaran Berbasis Projek Di SDN Sumobito 1 Jombang - Chasanah, Nur (Universitas Nusantara PGRI Kediri, 2023)
The general objective of this study is to describe periodic collaborative educational supervision in improving teacher performance in carrying out project-based learning at SDN Sumobito 1 Jombang for the 2022-2023 Semester 1 academic year. The method used in school action research is school action research with three cycles. The research subjects were 10 teachers at SDN Sumobito 1 Jombang for the 2022-2023 Semester 1 academic year. The research started from August to November 2022. The data collection method used interviews and documentation. The conclusion from the results of this study is that periodic collaborative educational supervision in improving teacher performance implementing project-based learning at SDN Sumobito 1 Jombang for the 2022-2023 Semester 1 academic year is carried out collaboratively which has an impact on improving performance.